Mahathir to receive honorary doctorate for Malay leadership - Borneo Post, (KK) (The Borneo Post, 2012)
SURAKARTA (Indonesia): Former prime minister Tun Dr Mahathir Mohamad is scheduled to receive an Honorary Doctorate in Social and Cultural Studies for Malay Leadership and Empowerment by Universiti Sebelas Maret Indonesia (UNSSolo) in a special ceremony at the university's main campus here on Monday.